An Impact of Campus to Corporate Recruitment Transition on Education Institute - Study of Tamilnadu State: Examining the Impact of Transition on Education Institutes in Tamilnadu State (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The fundamental skills obtained by the students at the school levelimpacts the career of students, additional curricular activities like technicalevents, arts, sports and games has an impact on their overall personalitydevelopment. In this paper we focused about the opinion of corporateorganizations towards the campus to corporate recruitment transition.Transition is important for an educational institute and useful for evaluatingthe quality of the education, faculty members and skill training for the bothtechnical as well communication.